Investigations of building elements with high—thermal resistance for additional insulation from the inside/Statybinių detalių, skirtų pastatams apšiltini iš vidaus, tyrimai - Puodžiukynas, Rimvydas; Puodžiukynienė, Milda (Journal of Civil Engineering and Management, 2000)
An effective decrease of investments in additional insulation of buildings could be achieved by insulation from the inside by special building elements with high—thermal resistance. It is suggested by the authors to produce such elements from expanded polystyrene with additives decreasing combustibility. The insulating elements could be of two types:1) large expanded polystyrene boards (equal to the height of rooms) and 5.5 or 8.5 cm thickness and 18 or 25 kg/m3 density from one side covered by 2 mm layer of polymergypsum plaster and glass fibre with textured surface;2) insulating combined blocks of 25 cm width and 40–100 cm length and thickness of 7 or 10 cm, where expanded polystyrene board with thickness of 5.5 or 8.5 cm is covered by 0,75 layer of polymergypsum plaster. The description of such combined insulating elements construction is presented in the paper as well as the research data of physical-mechanical, thermal properties and test results on combustibility. The investigation data are summarised in 2 Tables and 7 Figures. As the conclusion, the recommendations for additional insulation blocks of flats from the inside by combined insulating boards and blocks are presented. Then the thermal resistance of external expanded clay concrete walls could be increased up to 2.0–2.1 m2 · K/W, applying the insulating elements with thermal resistance of 1.3–1.4 m2·K/W and thermal resistance of ceramic brick masonry – up to 3.0–3.1 m2·K/W, applying insulating elements with thermal resistance of 2.0–2.1 m2 · K/W. The test results on combustibility which the elements under discussion are recognised as material with low fire spread and could be applied as the insulation inside buildings, are presented. The results of economical calculations are presented too. It is pointed out that the proposed additional insulating blocks of flats from the inside by suggested insulating elements with high—thermal resistance is significantly cheaper in comparison with the well-known external insulation.Article in Lithuanian.First Published Online: 26 Jul 2012